2022
DOI: 10.1073/pnas.2120691119
|View full text |Cite
|
Sign up to set email alerts
|

sEH-derived metabolites of linoleic acid drive pathologic inflammation while impairing key innate immune cell function in burn injury

Abstract: Significance Oxylipins alter immune cell function and potentially drive pathophysiology in burn and sepsis patients. Past and recent data reveal a correlation between increased systemic EpOME levels and reduced survival in human burn trauma and sepsis. This work extends these studies and provides evidence that the downstream sEH-derived metabolites, DiHOMEs, are driving worsening outcomes by altering the immune response. Inhibiting DiHOME metabolite formation with the sEH inhibitor, 1-trifluoromethox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…These studies support our finding that there was an increase in proliferation and angiogenesis in mice fed the ω-6-rich diet compared to the PUFA-balanced diet and the control mice groups. In addition, in mice fed the ω-6-rich diet, we found elevated levels of LA oxylipins such as EpOMEs and DiHOMEs, although they were not significant, it is important to note that these oxylipins participate in inflammatory processes, vascular permeability, neutrophil chemotaxis, as well cytotoxic effects in advancing acute and chronic inflammatory diseases [ 64 ]. Interestingly, McReynolds et al reported that patients with severe COVID-19 who show evidence of hyperinflammation mainly showed high levels of 9,10 and 12,13-DiHOMEs, compared with healthy controls [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies support our finding that there was an increase in proliferation and angiogenesis in mice fed the ω-6-rich diet compared to the PUFA-balanced diet and the control mice groups. In addition, in mice fed the ω-6-rich diet, we found elevated levels of LA oxylipins such as EpOMEs and DiHOMEs, although they were not significant, it is important to note that these oxylipins participate in inflammatory processes, vascular permeability, neutrophil chemotaxis, as well cytotoxic effects in advancing acute and chronic inflammatory diseases [ 64 ]. Interestingly, McReynolds et al reported that patients with severe COVID-19 who show evidence of hyperinflammation mainly showed high levels of 9,10 and 12,13-DiHOMEs, compared with healthy controls [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, as illustrated, the ELISA exhibits excellent sensitivity towards 12,13-DiHOME, which tends to be the endogenously predominant regioisomer 34 and has been associated with a broader range of biologies. 14,15,19,21–23 Incidentally, there is a commercially available competitive ELISA kit for 12,13-DiHOME (Cayman Chemical #501720). Nonetheless, the current assay possesses considerably greater detectability (≈7-fold higher than reported value) towards 12,13-DiHOME and is significantly more economical.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] However, studies utilizing EH-decient systems and sEH inhibitors indicated hydrolytic bioactivation of LTXs is necessary for exertion of toxic effects, hence implicating the DiHOMEs (or LTXDs) as the deleterious agents. [8][9][10] DiHOMEs cause extensive vascular permeability 11 and are involved in inammatory diseases, [12][13][14][15] pulmonary damage, 16 sepsis, 17 peroxisomal disorders, 18 and burn injury, 19 with high concentrations closely correlating with worsening morbidities. Recently, elevated plasma DiHOMEs were found to be excellent predictors of severe disease outcomes in patients with coronavirus disease 2019 (COVID-19).…”
Section: Introductionmentioning
confidence: 99%
“…EpOME and diHOME modulate vascular permeability and stimulate neutrophil chemotaxis ( 48 ). DiHOMEs are cardioprotective at low concentrations, but at higher levels, they have been implicated in vascular permeability and as cytotoxic agents and are associated with acute respiratory distress syndrome in patients with severe COVID-19 ( 51 , 52 ). diHOME serum concentrations were significantly elevated in burn-injured mice; however, this elevation was reduced by the administration of 1-trifluoromethoxyphenyl-3-(1-propionylpiperidin-4-yl) urea, which is a sEH inhibitor ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…DiHOMEs are cardioprotective at low concentrations, but at higher levels, they have been implicated in vascular permeability and as cytotoxic agents and are associated with acute respiratory distress syndrome in patients with severe COVID-19 ( 51 , 52 ). diHOME serum concentrations were significantly elevated in burn-injured mice; however, this elevation was reduced by the administration of 1-trifluoromethoxyphenyl-3-(1-propionylpiperidin-4-yl) urea, which is a sEH inhibitor ( 52 ). The inhibition of in vivo sEH can also block the toxicity of linoleate epoxides by stabilizing anti-inflammatory long-chain EpFAs and blocking the formation of the leukotoxin diols ( 53 ).…”
Section: Discussionmentioning
confidence: 99%